Multidimensional Service Quality in Private English Course Institutions: A Student Perception-Based Evaluation - Mudhofir Mudhofir; Abylai Ualikhanuly (Journal of Language, Literature, and Educational Research, 2025)
Purpose of the study: This study aims to evaluate multidimensional service quality in a private English course institution based on students’ perceptions and to categorize the performance level of each service dimension using percentage-based evaluation criteria. Methodology: This study employed a quantitative descriptive design using a structured Likert-scale questionnaire consisting of ten service quality dimensions. Data were collected through a survey of active students using total sampling. Data analysis applied descriptive statistical techniques and percentage calculations to classify service performance into categorical levels. Main Findings: The findings indicate that overall service quality is categorized as good to very good. The highest ratings were obtained in official certificates and diplomas, effective small-class systems, and course consultant facilities. Replacement class availability received the lowest percentage, although still categorized as good, indicating areas requiring service optimization. Novelty/Originality of this study: This study offers an integrated multidimensional service quality evaluation model specifically for private English course institutions using percentage-based categorical mapping. It advances existing research by combining academic, infrastructural, administrative, financial, and certification dimensions into a unified and practical institutional performance framework.